CD2–CD58 interactions are pivotal for the activation and function of adaptive natural killer cells in human cytomegalovirus infection. Issue 10 (29th August 2016) - Rölle, Alexander; Halenius, Anne; Ewen, Eva‐Maria; Cerwenka, Adelheid; Hengel, Hartmut; Momburg, Frank
Abstract : Human cytomegalovirus (HCMV) infection upregulates CD58. The subsequent interaction between CD2 on NKG2C + adaptive NK cells and CD58 on infected cells co‐stimulates antibody‐triggered NK‐cell activation and cytokine release. Abstract : The existence and expansion of adaptive NK‐cell subsets have been linked to HCMV infection. Phenotypically, a majority of adaptive NK cells expresses the activating receptor NKG2C and CD57. Some of the molecular factors driving the expansion of NKG2C + CD57 + NK cells in HCMV infection have been identified. The direct interaction of adaptive NK cells with HCMV‐infected cells, preceding the expansion, however, remains less studied. Recently, adaptive NK cells were reported to express higher levels of the co‐activating receptor CD2. We explored whether CD2 was directly involved in the response of adaptive NK cells to HCMV. In a co‐culture system of human PBMCs and productively infected fibroblasts, we observed an upregulation of CD69, CD25, and HLA‐DR on all NK cells. However, only in adaptive NK cells was this increase largely blocked by antibodies against CD2 and CD58. Functionally, this blockade also resulted in diminished production of IFN‐γ and TNF‐α by adaptive human NK cells in response to HCMV‐infected cells. Our results demonstrate that binding of CD2 to upregulated CD58 on infected cells is a critical event for antibody‐mediated activation and subsequent effector functions of adaptive NKG2C + CD57 + NK cells during the antiviral response.